Avaliação de genitoras sexuais de Brachiaria ssp. Na época de seca. - Pandolfi Filho, Antonio Delunardo (2014)
Currently Brazil is the largest producer and exporter of tropical forage seeds in Latin America where demand for quality and quantity of seeds have been driving the entire production chain. This study aimed to evaluate sexual interspecific hybrid populations aiming at selecting genitors to assist in diversification of cultivated tropical pastures of genus Brachiaria. The experiment was conducted at Embrapa Beef Cattle in Campo Grande-MS, in the period January-August 2013. Progenies of half-brothers test was performed, for selection between and within families, and selected the best genitors on the basis of progeny and also the best individuals within progenies. The experimental design was a randomized block with ten replicates and five plants were individually for production total dry matter and leaf, percentage of leaf, leaf:stem ratio and sprouting capacity. Adopting the selection intensity of 1% of the selected hybrids, 100% of the products are of the best cross progenitor, with gains selection ranging from 11.07% to 30.39%. These results allow us to affirm that it is possible to make a selection of the best individuals with significant gains in the breeding program.